Analisa Kualitas Mutu Beton Laboratorium dengan Pengujian Non Destruktif dan Destruktif - mufti saily (Jurnal Archipelago, 2024)
Abstract This research aims to compare the quality of concrete in the laboratory using non-destructive test (NDT) methods employing ultrasonic pulse velocity (UPVT) and hammer test, as well as destructive test (DT) methods utilizing compression testing machine (CTM). It was conducted at the Laboratory of Construction Materials and Equipment of the Public Works, Spatial Planning, and Land Affairs Agency of the Riau Islands Province with 60 concrete samples of various strengths (fc’ 30 Mpa, 36 Mpa, and 40 Mpa) at 28 days of age. The results indicate that UPVT provides strong conversions of concrete quality, while CTM approaches the planned concrete quality value. The comparison between the hammer test and CTM shows a moderate correlation, whereas UPVT and CTM exhibit a very strong correlation, with a high R2 value. Thus, concrete quality testing using UPVT and CTM yields reliable results close to the standards, while the hammer test is not recommended due to significantly differing results from the planned concrete quality standard. Keywords: Concrete, CTM, Destructive, Laboratory, UPVT.